A relationship between secondary and tertiary mathematics grades : a case study for foundation students - Fatin Amirah Ahmad ShukrI,; Aniza Wamin, Azuraini Mohd Arif,; Nabilah Fikriah Rahin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The achievements of students in mathematics or any mathematics course at the higher education level have declined in recent decades, even after the release of the Covid-19 pandemic. The purpose of this quantitative study is to determine the relationship between the Malaysian Certificate of Education (SPM) Modern Mathematics and Additional Mathematics grades and passing a high-level mathematics course at a university. The case study was conducted on 179 foundation-level of National Defence University of Malaysia (UPNM) students who enrolled in courses requiring knowledge of mathematics. Grades for SPM Modern Mathematics and SPM Additional Mathematics were collected using a checklist that students filled out. The dependent variable is measured by the results of the end-of-semester examination for the mathematics course. Descriptive analysis and correlation tests were conducted in this study. From the initial prediction, we may conclude that students with high marks in high school subjects will likewise perform well in their tertiary studies. Nonetheless, the correlation test reveals that it is not particularly significant. There is no conclusive evidence of the correlation between SPM Modern Mathematics grades and tertiary mathematics course performance. Considering this, a comparison of the data between SPM Additional Mathematics grade and tertiary mathematical topics revealed a positive association between the two. However, the correlation between SPM Mathematics and tertiary mathematics is relatively weak, with a Pearson correlation of 36.3%. Specifically, the achievement of mathematics subjects in the foundation level is less likely to be affected by SPM Modern Mathematics and SPM Additional Mathematics achievement.